2019
DOI: 10.1128/jvi.00169-19
|View full text |Cite
|
Sign up to set email alerts
|

Broad Hemagglutinin-Specific Memory B Cell Expansion by Seasonal Influenza Virus Infection Reflects Early-Life Imprinting and Adaptation to the Infecting Virus

Abstract: Memory B cells (MBCs) are key determinants of the B cell response to influenza virus infection and vaccination, but the effect of different forms of influenza antigen exposure on MBC populations has received little attention. We analyzed peripheral blood mononuclear cells and plasma collected following human H3N2 influenza infection to investigate the relationship between hemagglutininspecific antibody production and changes in the size and character of hemagglutininreactive MBC populations. Infection produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 54 publications
(110 citation statements)
references
References 59 publications
(104 reference statements)
4
106
0
Order By: Relevance
“…The mPlex-Flu assay was performed as described previously [7,8,12] [7,12], and the standard curve for each influenza virus strain was generated by 1:4 serially diluting STD01 for each batch of samples. 50µL of the diluted sample was added into each reaction well.…”
Section: Mplex-flu Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…The mPlex-Flu assay was performed as described previously [7,8,12] [7,12], and the standard curve for each influenza virus strain was generated by 1:4 serially diluting STD01 for each batch of samples. 50µL of the diluted sample was added into each reaction well.…”
Section: Mplex-flu Assaymentioning
confidence: 99%
“…The influenza HA bead panel used in this study is shown in Table ??, comprising 33 separate rHAs. 50µL of bead mix was added to each well of the plate as previously described [7,8,12]. Plates were then incubated with gentle shaking for 2 hours at room temperature, and then washed (PBS + 1% Bris + 0.1% BSA).…”
Section: Mplex-flu Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, there was an induction of antibodies towards the conserved stalk region of HA[6,7]. Additionally studies have suggested a role of Memory B cells in these highly cross-reactive antibody responses[8,9].…”
Section: Introductionmentioning
confidence: 99%